2010
DOI: 10.1016/j.physbeh.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Early experience alters limbic forebrain Fos responses to a stressful interoceptive stimulus in young adult rats

Abstract: The present study examined whether manipulation of the early life experience of rat pups might alter the later ability of an interoceptive challenge to recruit central neural circuits that receive visceral sensory signals and generate stress responses. For this purpose, litters were exposed to daily maternal separation for either 15 min (MS-15) or 180 min (MS-180) from postnatal days (P)1 to P10. Pups in control litters were raised under standard conditions (i.e., no separations). Similar to previous reports i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…Our findings that juvenile rats with a developmental history of MS15 displayed less stress-induced Fos activation within the caudal PVN and dBNST concur with previous reports of attenuated Fos activation of hypothalamic and limbic forebrain regions in adult MS15 rats after stress (Abraham and Kovacs, 2000, Koehnle and Rinaman, 2010). Interestingly, the PVN region in which juvenile MS15 rats displayed a decrease in restraint-induced Fos is the same region in which juvenile MS15 rats display enhanced retrograde transynaptic viral transport from the stomach wall (Banihashemi and Rinaman, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings that juvenile rats with a developmental history of MS15 displayed less stress-induced Fos activation within the caudal PVN and dBNST concur with previous reports of attenuated Fos activation of hypothalamic and limbic forebrain regions in adult MS15 rats after stress (Abraham and Kovacs, 2000, Koehnle and Rinaman, 2010). Interestingly, the PVN region in which juvenile MS15 rats displayed a decrease in restraint-induced Fos is the same region in which juvenile MS15 rats display enhanced retrograde transynaptic viral transport from the stomach wall (Banihashemi and Rinaman, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…We previously had demonstrated that central neural Fos responses to systemic LiCl matured during postnatal development [126], suggesting that the circuits underlying these responses might be susceptible to alteration by manipulating pups’ early life experience during that period of maturation. Similar to previous reports in adult rats, adolescent rats (P35-45) with a developmental history of MS15 displayed less anxiety-like behavior on the elevated plus maze compared to control and MS180 rats [179]. MS15 rats tended to display fewer LiCl-activated neurons in most brain regions compared with rats in the other two rearing groups.…”
Section: 0 Early Experience Modifies Visceral Circuit Assemblysupporting
confidence: 85%
“…To test this idea, we examined whether MS15 and/or MS180 might alter the later ability of an interoceptive challenge to recruit central neural circuits that receive visceral sensory signals and generate stress responses [179]. We previously had demonstrated that central neural Fos responses to systemic LiCl matured during postnatal development [126], suggesting that the circuits underlying these responses might be susceptible to alteration by manipulating pups’ early life experience during that period of maturation.…”
Section: 0 Early Experience Modifies Visceral Circuit Assemblymentioning
confidence: 99%
“…What are the specific effects of microbial signals on plasticity of gene expression by vagal sensory neurons within the nodose ganglia, and on neurons within the REVIEW PHYSIOLOGY • Volume 33 • March 2018 • www.physiologyonline.org cNTS that carry gut-derived signals to higher brain regions? Furthermore, given the powerful impact of early life events on the developmental assembly and life-long function of central visceral sensory and motor circuits, stress responsiveness, and emotionality (15,88,129,130,206,208,255,262), it is critical to determine how pre-and postnatal stress exposure, maternal diet during pregnancy and lactation, offspring diet from infancy through adolescence, and other environmental factors affect gene expression and signal transmission in vagal sensory pathways from gut to brain.…”
Section: Discussionmentioning
confidence: 99%